Development of Electronic LKPD Problem Based Learning in Differentiated Learning of Ecosystem Material to Improve Critical Thinking and Collaboration Skills of High School Students Phase E - Achmad Fanji Alhusein; Anggi Tias Pratama (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to produce teaching materials in the form of electronic LKPD problem based learning on differentiated learning that is feasible, practical, and effective to improve critical thinking skills and student collaboration. This type of research is research and development with the ADDIE procedure. The research was conducted at SMA N 1 Jebus on class X students. Feasibility, practicality, and effectiveness tests were conducted to obtain research data. The field trial design used a quasi-experiment with a control group pretest-posttest design. The instrument feasibility test was assessed by material experts and media experts. Practicality was assessed by biology teachers and students. Product effectiveness was analyzed using descriptive and inferential statistics using the SPSS 29 MANOVA test and using n-gain score analysis. The results of this study are as follows: (1) The electronic LKPD problem based learning differentiated learning produced was declared to meet the feasibility based on the values obtained from the media expert validator of 90% (feasible) and the material expert validator of 100% (very feasible) to improve critical thinking skills and student collaboration in high school; (2) The electronic LKPD for problem based learning of differentiated learning produced meets practicality based on the biology teacher questionnaire in the limited trial, obtaining a score of 94.2% (very feasible) and the student response questionnaire was 90% (very feasible); (3) The electronic LKPD for problem based learning in differentiated learning of ecosystem material is effective in improving critical thinking and collaboration skills of class X SMA students based on the results of the MANOVA test.